PENGARUH MODEL PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD NEGERI 122379 PEMATANGSIANTAR - Simanjuntak, Melvin; Canni Loren Sianturi; Esra Yola Panjaitan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Mind Mapping learning model on the IPAS learning outcomes of fifth-grade students at SD Negeri 122379 Pematangsiantar. This research is a quantitative study, and its research design uses Pre-Experimental with a one-group pretest-posttest design. The population in this study was 20 fifth-grade students at SD Negeri 122379 Pematangsiantar. The sample was a saturated sample, namely 20 fifth-grade students at SD Negeri 122379 Pematangsiantar, consisting of 13 male students and 7 female students. The research data showed that the average pretest score was 39.2, and the posttest score was 79.65. Data analysis was obtained through a paired sample T-test, where the t-calculated value was 11.671 and the t-table value was 1.717, indicating that t-calculated > t-table. Therefore, Ha is accepted, and Ho is rejected. It can be concluded that the Mind Mapping learning model has an effect on the IPAS learning outcomes of fifth-grade students at SD Negeri 122379 Pematangsiantar.